DELINEASI RESERVOIR PANAS BUMI BERDASARKAN LITOLOGI, ALTERASI HIDROTERMAL DAN PROFIL TEMPERATUR - -, Cyrke A.N. Bujung; -, Alamta Singarimbun; -, Dicky Muslim; -, Febri Hirnawan; -, Adjat Sudradjat (Fakultas Teknik Geologi Universitas Padjadjaran, 2010)
This study aims to delineate the breadth and depth of the geothermal reservoir and the resulting temperature. The method used is a compilation of lithology, alteration and the temperature profile that is supported by literature references and well data. Delinasi prospect area and deep reservoir of data viewed by lithology, alteration and the temperature profile. Regional prospects in the region of 2000C or more temperatures are also characterized by the presence of epidote minerals and are on lava and pyroclastic stratigraphy perselingan. The results obtained two different reservoir sites, the first located at depths of 800-1300 m above sea level and an area reached 1.37 x 107 m2., While the second is located at a depth (900 m - bottom) and an area of more than 3, 38 x 106 m2. Based on the temperature profile, the type of prospect geothermal reservoir in this area is the type of dominance of steam. .